Ectropion and Conjunctival Mass in a Patient with Primary Bilateral Conjunctival Amyloidosis. (16th November 2016) - Meduri, Alessandro; Rechichi, Miguel; Mazzotta, Cosimo; Scalinci, Sergio Zaccharia; Jaroudi, Mahmoud O.
Abstract : Background. Amyloidosis is a group of disorders characterized by deposition of an extracellular protein, known as amyloid, in an abnormal fibrillar form with highly characteristic histopathologic staining properties. The clinical presentation can vary from a focal, localized lesion where amyloidosis has minor clinical consequences to extensive systemic disease that can involve any organ system of the body. Ocular amyloidosis can occur as a localized lesion or as a part of a systemic disorder. Conjunctival amyloidosis is an uncommon condition that is rarely associated with systemic disease. It may be a manifestation of an immunologic disorder. Case Report. We report the case of a patient with bilateral conjunctival amyloidosis who was referred to us with the suspicion of a malignant conjunctival lesion. Examination of both eyes showed a yellow-pink mass with prominent intrinsic vessels, subconjunctival hemorrhage, and ectropion of the left lower eyelid. Diagnosis of primary localized conjunctival amyloidosis was made based on histopathologic evaluation of incisional biopsy and negative systemic work-up. Conclusion. Ocular amyloidosis is a rare disease that is slowly progressive and has a wide variety of clinical presentations. Consequently, the clinical diagnosis is often overlooked or delayed. Definitive diagnosis is achieved through histopathologic evaluation of biopsy specimen.